(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
This paper is a brief portrait of the musician, pianist, composer and musicologist Juan Francisco Sans, as perceived by someone who had the privilege of sharing friendship and professional projects with him.